Pengaruh Desain Produk Dan Celebrity Endorser Terhadap Keputusan Pembelian Le Minerale Di Solo Raya - Anisa Suci Wulandari; Widia Yulianti; Zahroh Annisa Fikri; Tiara Deviansyah Al Farizza (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Water is one of the main basic human needs. Human water consumption needs reach 70% this causes humans consume large amounts of water. However, the availability of clean water is still limited, giving rise to bottled drinking water, one of which is Le Mineralee products. The purpose of this study was to determine the effect of product design and celebrity endorsers on purchasing decisions for Le Mineralee drinking water. a questionnaire with a Likert scale. The sampling method used purposive samples, with a total sample of 110. The analytical tool used in this research is to use the IBM SPSS Statistics version 23 program: 1) product design has significant effect on purchasing decisions, 2) celebrity endorser has a significant effect on purchasing decisions.